2022
DOI: 10.1027/1614-0001/a000352
|View full text |Cite
|
Sign up to set email alerts
|

General Intelligence and the Dark Triad

Abstract: Abstract. The dark triad of personality (D3) – consisting of psychopathy, Machiavellianism, and narcissism – is a set of socially aversive personality traits. All three traits encompass disagreeable behavior and a particular disregard for the well-being of others, but also a tendency to strategic and deceptive manipulation of social environments in order to attain one′s goals. To exercise these complex manipulations effectively it seems beneficial to have high cognitive abilities. Therefore, a meta-analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…We could not find substantial relations between cognitive ability and the facets of Mach, but cognitive abilities exhibited moderate relations with evasive and persuasive bullshitting and a large one with pseudo-profound bullshit sensitivity. These findings are consistent with previous studies demonstrating that Mach and intelligence are independent (Michels, 2022;Michels et al, 2020), that intelligence has a protective effect on falling for dubious information (Andersson et al, 2022;Čavojová et al, 2018) and that those with higher cognitive abilities are less likely to employ persuasive bullshitting (Littrell et al, 2021a(Littrell et al, , 2021b. However, unlike Littrell et al (2021aLittrell et al ( , 2021b, we found a positive multivariate link between cognitive abilities and evasive bullshitting (for an exception, see Littrell et al, 2021b, Study 2).…”
Section: The Role Of Cognitive Ability In the Detection Of Bullshitsupporting
confidence: 92%
“…We could not find substantial relations between cognitive ability and the facets of Mach, but cognitive abilities exhibited moderate relations with evasive and persuasive bullshitting and a large one with pseudo-profound bullshit sensitivity. These findings are consistent with previous studies demonstrating that Mach and intelligence are independent (Michels, 2022;Michels et al, 2020), that intelligence has a protective effect on falling for dubious information (Andersson et al, 2022;Čavojová et al, 2018) and that those with higher cognitive abilities are less likely to employ persuasive bullshitting (Littrell et al, 2021a(Littrell et al, , 2021b. However, unlike Littrell et al (2021aLittrell et al ( , 2021b, we found a positive multivariate link between cognitive abilities and evasive bullshitting (for an exception, see Littrell et al, 2021b, Study 2).…”
Section: The Role Of Cognitive Ability In the Detection Of Bullshitsupporting
confidence: 92%
“…Other examples, such as socioeconomic status or educational level, which were very homogeneous in the sample of this study, could be relevant variables to be taken into account. Other interesting variables include verbal intelligence, a construct with relevant direct relationships with personality [32] and also with indirect relationships with other potential moderating variables [33][34][35]. Moreover, the present study was conducted in the Spanish language, and further research should try to analyze the generalizability of the results in different languages and cultures.…”
Section: Discussionmentioning
confidence: 96%
“…In support, other studies have found interpersonal features of psychopathy are linked to violence (Hill et al, 2004; Olver et al, 2020). Relatedly, impulsive lifestyle and callous affect are associated with lower IQ (Michels, 2022; Salekin et al, 2004; Vitacco et al, 2005) and executive functioning (Baskin-Sommers et al, 2015), as well as worse emotion regulation (Garofalo et al, 2020), which in combination may increase the risk for violence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite early thinking that psychopathy was associated with adequate or perhaps higher intelligence (Cleckley, 1941), along with contemporary conceptualizations of criminal psychopathic masterminds (DeLisi et al, 2010; Furnham et al, 2009), studies have found little differences in IQ for those with versus without diagnostic psychopathy (Hare & Neumann, 2008; Johansson & Kerr, 2005). However, a recent meta-analysis found an inverse association between IQ and psychopathy, particularly affective traits (Michels, 2022; see also Salekin et al, 2004; Vitacco et al, 2005). Still, the literature is mixed as to whether there is an interaction of psychopathy and IQ that influences risk for criminal behaviors (Hampton et al, 2014; Heilbrun, 1982; Walsh et al, 2004), which we sought to further explore in the present study.…”
mentioning
confidence: 99%